STRUCTURAL ANALYSIS IN FRACTURED BASEMENT ROCK OF PUTERIFIELD USING ENHANCED MULTI-SEISMIC ATTRIBUTES WORKFLOW - KEE , SHOOK PENG (2018)
Hydrocarbon had been found in the fractured granitic basement around the Vietnam-Malaysia area, for example in Cuu Long Basin and Anding field where hydrocarbon is accidently found. For this study, Puteri is used as study area for testing. Puteri field is in north-eastern flank of Malay Basin, where hydrocarbon producing unit is located specifically in group I, J and K of the said basin. This project focuses on the fracture and fracture network delineation in Puteri basement using multiple seismic attributes via an improved workflow generated in PETREL. With the purpose to identify the faults, multi seismic attributes analyses through an enhanced workflow are used. The enhanced workflow has three (3) major components which are data filtering, attribute application and map generation.